Visualizing graphene edges using tip-enhanced Raman spectroscopy - Su, Weitao; Roy, Debdulal (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures, 2013)
The edges of a single layer graphene (SLG) flake play important roles in determining the electronic transport properties of graphene devices. Accurate determination of the phase-breaking lengths (Lσ) near the edges remains to be a significant challenge for near field optical measurements. This article presents an image of graphene edges using high resolution tip-enhanced Raman spectroscopy (TERS) of mechanically exfoliated SLG and reports the value of Lσ (4.2 ± 0.5 nm). The current near-field measurements verify the theoretical value of Lσ and highlight the potential of TERS in characterizing graphene at the nanoscale.